LAYANAN PEMERIKSAAN DAN PENGUMPULAN DATA KESEHATAN SISWA-SISWI KELAS VI BERBASIS SISTEM INFORMASI MENGGUNAKAN METODE FUZZY TSUKAMOTO - Jejen Jaenudin; Yuggo Afrianto; Yoga Hardi Firdaus (JPMUJ, 2023)
Health is an asset given by humans, therefore health is a very expensive value. Students who are facing the final exam as a condition of graduation, are expected to have a health condition to be able to take the exam and tutoring school National Examination. Therefore the results of observations in community service activities found the need for a system that is able to predict student health by collecting data on the health of any student included in the category of healthy, less healthy, and unhealthy by examining it. The method used in predicting uses Fuzy Tsukamoto's method and the client and server system development method. The test results obtained by examining 78 students and able to predict 60 people in the healthy category and 18 people sick.